Badan Hukum Gereja dan Good Church Governance - Prananingrum, Dyah Hapsari; Putri, Kezia Annabel Rinda (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
The existence of the church in the midst of life has 2 systems. First is the kingdom system of GOD which prioritizes the values ​​of Christ on the one hand and the social system and state system which still also has legal, economic and cultural entities on the other hand. In a state system, the church as a legal subject has the rights, obligations and authority to carry out legal acts and bear legal responsibilities The church has separate assets from the founder or owner and administrators which must be managed properly. One of the church's legal actions in the civil sector is managing church property, managing rights to land and buildings, making agreements with third parties such as building contractors, procuring goods and services. The method of this activity is through socialization, using Google Meet application. The target of this activity is the community within the Central Sulawesi Christian Church (GKST).